A Survey on the Challenges in Autonomic Computing - Ahuja, A (International Journal of Computer Sciences and Engineering, 2025)
With the advancement in technology, the emerging complexity of the systems require the development of a more intelligent system that can tackle the requirements of system/ software architectures in an efficient manner. The term ‘autonomic computing’ refers to the computing system that operates on its own or with the involvement of minimum human activity and paved the way for the system designers and system developers to develop such intelligent systems that can have adjusting capability. It completely revolutionized the area of research in the context of computing technologies. The goal of this paper is to provide insight overview of autonomic computing, followed by the challenges involved in its realization, and then applications and future application scope is discussed with the addressing of key issues.